Driving Innovation through Organisational Dynamics in Public–Private Partnerships - Simón Moya, virginia; Montesinos-Sansaloni, Eduard (JOINETECH, 2025)
This study explores how organisational attributes, such as seniority, workforce size, and thematic focus, shape innovative capacity and public funding outcomes for R&D&I projects under Spanish public–private partnership (PPP) frameworks. Drawing on organisational learning, infant industry, and public agenda theories, the analysis examines data from entities collaborating in R&D&I projects. Contrary to conventional assumptions, older organisations do not secure funding more frequently, although their accumulated expertise helps manage larger-scale, innovation-focused endeavours. Furthermore, while having a bigger workforce increases funding amounts, a past record of success in grant applications does not necessarily enhance outcomes, suggesting that each proposal’s innovative merit may be judged on its own terms. Surprisingly, proposals grounded in high-tech or social objectives attract similar funding levels, indicating that public agencies value diverse approaches to innovation that extend beyond technological paradigms. These findings underscore the complexity of advancing innovation in PPPs, highlighting the importance of organisational structure, thematic breadth, and strategic alignment with societal priorities. Implications for policymakers include fostering networks that blend social and technological innovations to address societal needs.
Keywords: public-private partnership; entrepreneurship; social economy